Pengaruh Kecukupan Modal, Penyaluran Kredit dan Ukuran Perusahaan Pada Profitabilitas Dengan Risiko Kredit Sebagai Pemoderasi - Trisha Dewi Parasthiwi, A. A.; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 26 No 1 (2019), 2019)
This research was conducted at banking companies listed on the Indonesia Stock Exchange in the period 2013-2017, which were 42 companies. The sampling technique in this study was taken based on non probability sampling method with purposive sampling technique so as to produce a sample of 32 companies. The data analysis technique used in this study was moderated regression analysis. Based on the results of the analysis it was found that capital adequacy has a positive effect on profitability, credit distribution has a positive effect on profitability and firm size has a positive effect on profitability. The results of this study also show that credit risk is not able to weaken the influence of capital adequacy and lending to profitability and credit risk is able to weaken the influence of company size on profitability. Keywords:  capital adequacy, credit distribution, company size, credit risk, profitability